Analisando a qualidade dos dados sobre mortes violentas no sim entre 2010 e 2021 - Daniel Cerqueira; Gabriel de Oliveira Accioly Lins (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The Mortality Information System (Sistema de Informaç\~oes sobre Mortalidade - SIM) is the only statistically reliable nationwide database that allows calculating the annual homicide rates for each Federative Unit (FU) since 1980. Concerning to data on violent deaths, two elements, however, may conspire against the quality of the information: the not filling of the characteristics of the victims and the conditions under which the incident occurred; and the number of violent deaths with undetermined cause (mortes violentas com causa indeterminada - MVCI). In this work, we analyzed the quality of data on violent deaths in the SIM between 2010 and 2021 for each FU, focusing on these two elements. We observed a deterioration in the data from 2019 onwards, in which the increase in MVCI may be hiding the true incidence of homicides.
Keywords: C38; C52; C40; 330; homicide; Mortality Information System; violent death with undetermined cause; Brazil